6(k+4)=3k-12

Simple and best practice solution for 6(k+4)=3k-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(k+4)=3k-12 equation:


Simplifying
6(k + 4) = 3k + -12

Reorder the terms:
6(4 + k) = 3k + -12
(4 * 6 + k * 6) = 3k + -12
(24 + 6k) = 3k + -12

Reorder the terms:
24 + 6k = -12 + 3k

Solving
24 + 6k = -12 + 3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-3k' to each side of the equation.
24 + 6k + -3k = -12 + 3k + -3k

Combine like terms: 6k + -3k = 3k
24 + 3k = -12 + 3k + -3k

Combine like terms: 3k + -3k = 0
24 + 3k = -12 + 0
24 + 3k = -12

Add '-24' to each side of the equation.
24 + -24 + 3k = -12 + -24

Combine like terms: 24 + -24 = 0
0 + 3k = -12 + -24
3k = -12 + -24

Combine like terms: -12 + -24 = -36
3k = -36

Divide each side by '3'.
k = -12

Simplifying
k = -12

See similar equations:

| -2x=3x+3 | | 5z-96z+2z+4=12z-156 | | 4x+1=.15 | | 12b+3whenb=-4 | | 1/3=954/s | | 6c=3(c+4)-c | | 5z-96z+2z+4=2(6z-78) | | 1.8=0.03x-58.32 | | 4x+35x=21x+28 | | 2+4(x-7)=5-4(x-5) | | 8x+47=8(x+6) | | -1+3x=3+25x | | 5(3m-4)-8=-88 | | f(x)=x^3-28x+48 | | 6(2x+5)=2 | | x^2+3y^2-3z^2-3xy-2xz-2yz=-1997 | | -3(2g+1)+3g=6g+3 | | 6z-38=130 | | 5n^2+2n-14=-7 | | 9x-58=7x | | (8x-16)=180 | | 5n^2+2n-14n=-7 | | (1/2)(5n-6)=3n | | -s+10=9s+6 | | y-2xy+4x=1 | | 10=(1/3)(w-15) | | 12y=3x-45 | | -2y-8+4x=0 | | x+6+x+6=3x-1 | | 3(x+22)=14-7(x) | | log^4(-x)=log^4(x+2) | | 4x-1=9x-21 |

Equations solver categories